A New Approach to Obtaining The Optical Indices From The Values of The Spectrophotometric Measurement - Bahadır Elmas; Ümit Özlem Akkaya Arıer (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Calculation of spectral transmittance and reflectance values of amultilayer coating need to be known the spectral refractive index and theextinction coefficient values. In order to calculate the spectral opticalindices a software was developed. It uses the spectrophotometric transmittanceand reflectance values of single layer coatings, each coated only with thematerial in question, and the thicknesses of these layers. Considering the effective functions itcontains, the software was written in the Matlab programming environment.